(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: In recent decades, English language teaching (ELT) has experienced a paradigm shift from teacher-centered traditional methods to learner-centered modern methodologies. This article presents an in-depth comparative analysis of traditional and modern approaches in ELT by examining their historical foundations, pedagogical principles, classroom applications, and practical effectiveness. Drawing upon educational theories and empirical studies, it explores the strengths and limitations of both approaches. The paper ultimately advocates for an eclectic approach that incorporates the advantages of both paradigms to meet diverse learner needs in contemporary educational settings.